2019
DOI: 10.1002/ange.201813315
|View full text |Cite
|
Sign up to set email alerts
|

Copper Photoredox Catalyzed A3’ Coupling of Arylamines, Terminal Alkynes, and Alcohols through a Hydrogen Atom Transfer Process

Abstract: The first successful example of the three-component coupling of N-alkylanilines,terminal alkynes,and alcohols was achieved at room temperature by av isible-light-mediated copper-catalyzed photoredox hydrogen-atom transfer process. This method allows preparation of propargylamines through uniquely selective a-C À Hb ond activation of unactivated alkylalcohols.P reliminary studies indicate that formation of a-oxy radical is operative.T his approach facilitates rapid access to biologically important propargylamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…[15][16][17][18] Past few years, visible light mediated metal and metal-free photoredox catalysts have been employed for α C(sp 3 )À H functionalization of alcohols. [19][20][21][22][23][24] For examples, in 2019, Xu et al [25] has reported visible light mediated one pot synthesis of quinazolinones by selective oxidation of alcohols via hydrogen atom transfer (HAT) using organic dye as photosensitizer. Recently, Sarma et al [26] developed visible light mediated synthesis of quinazolinones and quinoxalines in the presence of TBHP as an oxidizing agent in aqueous medium without photoredox catalysts.…”
mentioning
confidence: 99%
“…[15][16][17][18] Past few years, visible light mediated metal and metal-free photoredox catalysts have been employed for α C(sp 3 )À H functionalization of alcohols. [19][20][21][22][23][24] For examples, in 2019, Xu et al [25] has reported visible light mediated one pot synthesis of quinazolinones by selective oxidation of alcohols via hydrogen atom transfer (HAT) using organic dye as photosensitizer. Recently, Sarma et al [26] developed visible light mediated synthesis of quinazolinones and quinoxalines in the presence of TBHP as an oxidizing agent in aqueous medium without photoredox catalysts.…”
mentioning
confidence: 99%